2022
DOI: 10.3390/min12050615
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sc Concentrations in Ni-Co Laterites Using Al as a Geochemical Proxy

Abstract: Scandium (Sc) is used in several modern industrial applications. Recently, significant Sc concentrations (~100 ppm) were reported in some nickel-cobalt lateritic ores, where Sc may be valuably co-produced. However, Sc is typically not included in routine analyses of Ni-Co ores. This contribution examines the relevance of using routinely analysed elements as geochemical proxies for estimating Sc concentration and distribution. Three Ni-Co lateritic deposits from New Caledonia were investigated. In each deposit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Such mineralogical distribution leads to fractures characterized by high Ni content ranging from more than 10 wt.% to 30 wt.%, and almost no Mg (<1 wt.%), while the matrix is characterized by Ni content ranging from 1 wt.% to 6 wt.%. These results are consistent with field observations where fractures present high Ni concentrations ranging from 10 wt.% to 40 wt.% (Cathelineau et al, 2016(Cathelineau et al, , 2017, while Ni grades do not exceed 2 to 4 wt.% in porous matrix (Butt & Cluzel, 2013;Cathelineau et al, 2016;Teitler et al, 2019Teitler et al, , 2022.…”
Section: Impact Of Fractures On the Dual Porosity Modelsupporting
confidence: 91%
“…Such mineralogical distribution leads to fractures characterized by high Ni content ranging from more than 10 wt.% to 30 wt.%, and almost no Mg (<1 wt.%), while the matrix is characterized by Ni content ranging from 1 wt.% to 6 wt.%. These results are consistent with field observations where fractures present high Ni concentrations ranging from 10 wt.% to 40 wt.% (Cathelineau et al, 2016(Cathelineau et al, , 2017, while Ni grades do not exceed 2 to 4 wt.% in porous matrix (Butt & Cluzel, 2013;Cathelineau et al, 2016;Teitler et al, 2019Teitler et al, , 2022.…”
Section: Impact Of Fractures On the Dual Porosity Modelsupporting
confidence: 91%
“…In addition to Ni ore and economic contents of Co, the Ni(Co) laterite deposits host critical metals or high-tech elements that are increasingly demanded by many industries. These deposits are becoming worth targets for Sc, REE, and PGE [94,[113][114][115][116][117]. Recent studies have shown that Ni(Co) laterite deposits from the Caribbean, Balkan, and Pacific regions are enriched in critical metals (e.g., REE, PGE, and Sc) that could be economically extractable [94,[116][117][118].…”
Section: Research Perspectivesmentioning
confidence: 99%
“…These deposits are becoming worth targets for Sc, REE, and PGE [94,[113][114][115][116][117]. Recent studies have shown that Ni(Co) laterite deposits from the Caribbean, Balkan, and Pacific regions are enriched in critical metals (e.g., REE, PGE, and Sc) that could be economically extractable [94,[116][117][118]. However, few studies have been conducted on the occurrence and distribution of Sc, REE, and PGE in Ni(Co) laterite deposits of SE Asia (see Section 4).…”
Section: Research Perspectivesmentioning
confidence: 99%
“…When peridotites are submitted to a hot and humid climate, the complete olivine dissolution yields a residual soil, the laterite. The latter is formed essentially of goethite and hematite due to the very low solubility of Fe 3+ iron oxides and hydroxides under oxidising conditions [11][12][13][14]. In the lower part of the lateritic profile, Mg-Ni-silicates form at the boundary with the bedrock in the so-called saprolite horizon [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is formed essentially of goethite and hematite due to the very low solubility of Fe 3+ iron oxides and hydroxides under oxidising conditions [11][12][13][14]. In the lower part of the lateritic profile, Mg-Ni-silicates form at the boundary with the bedrock in the so-called saprolite horizon [12,14]. The homogeneous lowering of the weathering front and the generation of a weathering horizon of several tens of meters thick implies a duration of at least 10 Ma [15,16].…”
Section: Introductionmentioning
confidence: 99%